A produção decisória do sistema de justiça criminal para o crime de homicídio: análise dos dados do estado de São Paulo entre 1991 e 1998 - Ludmila Ribeiro (Universidade do Estado do Rio de Janeiro, 2010)
The aim of this article is to analyze how the São Paulo criminal justice system handles homicide cases reported through the State's police precincts (from 1991 to 1998) and the respective law enforcement and legal ramifications. The data were obtained from the Seade Foundation database. Using this information, the study showed that non-legal variables like color and age play a key role in understanding the system's rulings and sentences in murder cases.